Obesity relations with a score of oral hygiene index simplified in adolescents aged 16-18 years in SMAN 1 Surakarta - Vinariyanti, Erika; Subiyantoro, Pradipto; Aryoseto, Lukman (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Background : Indonesia is currently faced by dual nutrition problems , which prevalence of obesity had increased. Obesity is often associated with aspects of oral health. Oral hygiene is important to be maintained because it can affect the overall health of the body so as to be one indicator of a persons general health. Behavioral factors play an important role in influencing the status of oral hygiene habits such as eating sugary or high - carbohydrate food. This study aimed to determine the relationship between obesity and a score oral hygiene index simplified in adolescents aged 16-18 years in SMAN 1 Surakarta by controlling confounding factors in brushing teeth habit, salivary pH and composition of dental students. Methods: This study was an observational analytical research using cross sectional approach. Sampling technique was used purposive sampling which the sample size was 30 students age 16-18 years old in SMAN 1 Surakarta taken in November 2015. Data z-score was obtained through the measurement of height and weight, whereas oral hygiene status was measured by the score of oral hygiene index simplified. Data analysis technique was Kolmogorv-Smirnov test and test correlation using contingency coefficient test. Data were processed by SPSS 20.00 for Windows. Results: This results showed there was a significant relationship between obesity with a score of oral hygiene index simplified in adolescents aged 16-18 years in SMAN 1 Surakarta (p = 0,003). The contingency coefficient test showed there was a strong uphill linear relationship between obesity with OHIS score (r = 0,619) Conclusion: This study concluded that there was a relationship between obesity with a score of oral hygiene index simplified in adolescents aged 16-18 years in SMAN 1 Surakarta. Keywords: Obesity, Oral Hygiene